Genotype number and allelic diversity overview in the national collection of Chilean potatoes - Muñoz, M.; Folch, C.; Rodríguez, F.; Kalazich, J.; Orena, S.; Santos, J.; Vargas, R.; Fahrenkrog, A.; Puga, A. (Springer, 2016)
Chile is the origin of the Solanum tuberosum group Chilotanum corresponding to lowland tetraploid landraces. The most complete morphological description of the Chilean germplasm was published in 2008 in the Catalogue of Varieties of Native Potatoes from Chile, which describes 211 varieties. Two institutions of the Chilean government, INIA and SAG (Agricultural and Livestock Service of Chile), keep collections of 332 and 257 accessions, respectively; the varieties registered in the catalogue are included in the SAG collection. Thus, an important gap occurs between the number of varieties listed in the National Catalogue of Chile and the number of traditional varieties found in the Chilean collections of potatoes. In this work, two national collections of Chilean native germplasms (INIA-Remehue and SAG) were analysed via four microsatellite markers with the aims of (1) discriminating different genotypes in order to more accurately catalogue the current number of native Chilean varieties, (2) evaluating the diversity of genotypes potentially known with the same nomenclature by farmers, and (3) comparing allelic diversity of native germplasm with 44 commercial varieties. Of the 589 native accessions analysed, 320 different allelic phenotypes were found indicating that there are at least 320 different genotypes in the collections. Of these, 158 belonging to the INIA collection were not found in the SAG collection. These 158 new genotypes should increase the number of known Chilean varieties. As expected, different genotypes were known under the same popular name. In terms of allelic diversity, the group of commercial varieties contained a subset of the alleles within the collection of SAG and INIA-Remehue.